122 ST elevation myocardial infarction due to stent thrombosis is associated with worse clinical outcomes than STEMI due to coronary thrombosis. (22nd September 2015) - Jones, D A; Rathod, K; Guttmann, O; Wicks, E; Jain, A; Knight, C; Rothman, M T; Mathur, A; Wragg, A
Abstract : Background: Stent thrombosis (ST) is a recognised cause of ST Elevation Myocardial infarction (STEMI) in patients with previous percutaneous coronary interventions (PCI). The incidence is increasing and to date outcomes are not well characterised. We therefore sought to compare STEMI caused by ST vs de novo coronary thrombosis to evaluate procedural risk and clinical outcome. Method: Clinical information was analysed from a prospective database on 1718 patients who underwent Primary PCI following STEMI between October 2003 and March 2009 at a London centre. Information was entered at the time of procedure and outcome assessed by all-cause mortality information provided by the Office of National Statistics via the BCIS CCAD national audit. Results: Stent thrombosis (ST) accounted for 6.9% (119/1718) of all STEMIs with a frequency that has increased over time (5.4% in 2005 to 9.8% 2008). Drug-eluting stents (DES) accounted for 42% of ST overall and 67% over the past 3 yrs. ST occurred early (0-30d) in 30% (36/119), late (30d-1 yr) in 31% (37/119) and very late (> 1 yr) in 39% (46/119) of pts. Pts with ST compared to native artery occlusion had higher rates of previous MI (50.9% vs 12%, p<0.0001) and previous CABG (6% vs 2.4%, p=0.002). There was no difference in age, diabetes or cardiogenic shock. Pts with STEMI due to ST had higher in-hospital MACE (9% vs 2%, p= 0.0001), MACE at 1 year (21% vs 9%, p<0.0001), this persisted up to 3 years (26% vs 10%, p<0.0001). MACE was driven by higher rates of MI (4% vs 1%, p=0.0007), TVR (12% vs 2%, p<0.0001) and death (15% vs 6%, p=0.0001). Conclusion: Stent thrombosis accounts for an increasing proportion of STEMI and is associated with worse outcomes compared with native artery occlusion. New strategies are needed to address this growing problem.